2005
DOI: 10.1074/mcp.m400192-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

A Proteomic Microarray Approach for Exploring Ligand-initiated Nuclear Hormone Receptor Pharmacology, Receptor Selectivity, and Heterodimer Functionality

Abstract: Nuclear hormone receptors (NHRs) are major regulators of development and homeostasis in multiple organ systems. These proteins are ligand-modulated transcription factors that regulate gene expression in response to changes in circulating levels of their cognate hormones or hormone analogs. When NHRs bind ligands, they adopt distinct conformations that enable or disable the binding of coregulator proteins in a manner that reflects the agonist versus antagonist character of the ligand. Using the estrogen recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 49 publications
4
28
0
Order By: Relevance
“…The NdeI-BamHI fragment of the NCoRC' from the GST-NCoRC' vector was excised and cloned into the NdeI and BamHI sites of pET15b vector and expressed as a 6XHis fusion protein. Expression of the NRID fragment of hSRC3 protein (residues 627-829) has been previously described (23). The NRID fragments of SRC3 and NCoR were fluorescently labeled with 5-iodoacetamidofluorescein according to our published procedure (23,24).…”
Section: Plasmids and Protein Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…The NdeI-BamHI fragment of the NCoRC' from the GST-NCoRC' vector was excised and cloned into the NdeI and BamHI sites of pET15b vector and expressed as a 6XHis fusion protein. Expression of the NRID fragment of hSRC3 protein (residues 627-829) has been previously described (23). The NRID fragments of SRC3 and NCoR were fluorescently labeled with 5-iodoacetamidofluorescein according to our published procedure (23,24).…”
Section: Plasmids and Protein Expressionmentioning
confidence: 99%
“…Expression of the NRID fragment of hSRC3 protein (residues 627-829) has been previously described (23). The NRID fragments of SRC3 and NCoR were fluorescently labeled with 5-iodoacetamidofluorescein according to our published procedure (23,24). …”
mentioning
confidence: 99%
“…Unlike previous studies of ER-coactivator interactions, which used a synthetic peptide containing a single LXXLL motif as the coactivator component (21)(22)(23), our use of a complete NRID fragment of SRC3 in the present study resulted in binding curves displaying clear saturation for all of the estrogens and revealed considerable variations in affinities. The ERā£ and ERā¤ LBDs and SRC3 NRID peptide fragments used in the present study have been extensively characterized in a number of our previous studies that demonstrated that these fragments displayed functional characteristics very similar to full-length ERs in terms of ligand binding and ligand-specific conformational and receptor dimerization changes as well as agonist/antagonist-regulated coactivator recruitment profiles (15,17,18,(27)(28)(29). The subnanomolar sensitivity with which our tr-FRET assay measures SRC3-ER interaction, together with nearly stoichiometric binding of SRC3 to ER at equilibrium with an EC 50 of 0.88 nM for ERā£ and 0.76 nM for ERā¤ in the coactivator titration assay, supports the fact that the ER LBDs and SRC3 NRID fragments that we have used retain most if not all of the receptor-coactivator interaction properties of full-length ER and SRC3 proteins.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the weakness of cell-free protein expression approaches is the lack of post-translational modifi cations and appropriate folding of some proteins (7). However, it was suggested that addition of chaperonin GroEL can alleviate those problems (45).…”
Section: Library Construction and Protein Purifi Cationmentioning
confidence: 99%
“…In addition, a high-throughput method of fl uorescence labeling of full-length cDNA products has been reported (45). The labeling relies on fl ourophore-tagged puromycin in conjunction with either a release factor-free expression system or exclusion of stop codons.…”
Section: Library Construction and Protein Purifi Cationmentioning
confidence: 99%